Cohort Study Comparing the Berg Balance Scale and the Mini-BESTest in People Who Have Multiple Sclerosis and Are Ambulatory. Issue 9 (1st September 2016) - Ross, Elaine; Purtill, Helen; Uszynski, Marcin; Hayes, Sara; Casey, Blathin; Browne, Catherine; Coote, Susan
Abstract: Background: The Berg Balance Scale (BBS) is a balance measure commonly used for people with multiple sclerosis (MS). The Mini-BESTest is an alternative based on balance systems. Objective: The study objective was to compare the BBS and the Mini-BESTest for sensitivity to change, likelihood ratios for walking aid use and falls, and associations with clinical variables in people who have MS and are ambulatory. Design: This was a cohort study with measurements before and after exposure to 8 weeks of routine physical therapy intervention. Methods: For 52 participants who had a primary diagnosis of MS and who were independently mobile, with or without an aid, demographic details and a history of falls and near falls were collected. Participants completed the Mini-BESTest, Multiple Sclerosis Impact Scale-29, Multiple Sclerosis Walking Scale-12, BBS, Modified Fatigue Impact Scale, and Six-Minute Walk Test. Results: No participant started with a baseline Mini-BESTest maximum score of 28, whereas 38.5% (n=20) started with a baseline BBS maximum score of 56. Statistically significant changes in the Mini-BESTest score (X̅=5.31, SD=3.5) and the BBS score (X̅=1.4, SD=1.9) were demonstrated. Effect sizes for the Mini-BESTest and the BBS were 0.70 and 0.37, respectively; standard response means for the Mini-BESTest and the BBS were 1.52 and 0.74, respectively. Areas under the receiver operating characteristic curves for the Mini-BESTest and the BBS were 0.88 and 0.77, respectively, for detecting mobility device use and 0.88 and 0.75, respectively, for detecting self-reported near falls. The Mini-BESTest had a higher correlation for each secondary measure than did the BBS. Limitations: This study involved a sample of convenience; 61% of the participants did not use a walking aid. The order of testing was not randomized, and fall status was obtained through retrospective recall. Conclusions: The Mini-BESTest had a lower ceiling effect and higher values on responsiveness tests. These findings suggest that the Mini-BESTest may be better at detecting changes in balance in people who have MS, are ambulatory, and have relatively little walking disability.